Coyuntura Económica - Elizabeth Aponte Jaramillo; Ivarth Palacio Salazar; Holmes Sánchez Rengifo; Avelino Martínez Sandoval; Martha Vázquez Olave (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2005)
Coyuntura Económica